Performances of Barbarine ewes grazing on wheat stubble under conventional and conservation agricultural conditions in a Tunisian semi-arid area - Guesmi H.; Moujahed N.; Ben Youssef S.; Darej C.; Chakroun M.; Ben Salem H. (Innovation for sustainability in sheep and goats, 2019)
The aim of this work was to study the effect of agricultural practices (Conventional and conservation agriculture: Conv.A and CA respectively) on live weight variation and body condition scoring (BCS) of Barbarine ewes in Tunisian semi-arid conditions. The trial was carried out in the experimental station of INRAT (Region of Zaghouan) in two plots of bread wheat stubble, cultivated respectively according to Conv. A and CA conditions. Each one was dividedinto 3 electrically fenced subplots and each subplot had an area of 1665 m2 for a stocking rate of 30 ewes/ha.Thirty Barbarine breed ewes (Initial average weight 38 ± 1.86 kg) were divided into 6 homogeneous groups of 5 ewes each (3 groups for each agricultural system: Conv.A and CA). Animals grazed during a period of 45 days. Live Weight (LW), Daily Live Weight Gain (DLWG) were determined 4 times after the start of the experiment (every 10 days) and BCS was determined at the beginning of the experiment and 40 days after. Results showed that Live Weight increased significantly from the first weighing time until the end of the experiment both in Conv. A and CA (P<0.05, + 3.94 and 3.85 kg respectively). In the second period, DLWG decreased significantly in CA plot (P<0.05, -40.1 g/d), affecting the body weight which decreased but not significantly. Then, the live weight increased in the third period and it was maintained until the end of the experiment with a positive DLWG registered on ewes. The same trends of variation in LW were found in Conv.A and CA. For all the weighing times, no differences in LW and DLWG values between agricultural practices were noted. Results relative to BCS variation showed that no significant differences were observed in lumbar region score between the two investigated agricultural practices in the 2 measurement periods. The variation of tail region score according to agricultural practices at the start and the end of experiment showed that both in Conv. A and CA, the tail region score increased significantly (P<0.01; P<0.0001, respectively for Conv. A and CA).Statistically, the two investigated agricultural practices (Conv.A and CA) didn’t affect the tail region score whatever the measurement time. It was concluded that in these experimental conditions, no differences were found in performances between the two agricultural practices.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)